2005
DOI: 10.1089/neu.2005.22.1003
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury Induces Persistent Cognitive Deficits and Behavioral Disturbances in Mice

Abstract: Victims of mild traumatic brain injury (mTBI) do not show clear morphological brain defects, but frequently suffer from long-lasting cognitive deficits, emotional difficulties and behavioral disturbances. In the present study, we investigated the effects of experimental mTBI in mice on cognition, spatial and non-spatial tasks, and depressive-like behavior in mice. Experimental brain injury was induced using a concussive head trauma, which creates the TBI by a weight-drop device. Different groups of mice were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
136
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 29 publications
16
136
0
Order By: Relevance
“…The forced swimming test (FST) was designed as a primary screening test for antidepressants, but the sensitivity of the FST in detecting TBI-induced depression has not been consistent. Although depression-like behavior during the FST has been reported previously in a mild TBI model using weight drop (Milman et al, 2005;Shapira et al, 2007), it was not detected in our current mouse TBI model, or in the fluid-percussion injury model ( Jones et al, 2008). Potential contributing factors to the differential detection of depression-like behavior by FST after brain injury may lie in differences in the models and severity of experimental TBI, the timing of the affective measures used following injury, and/or other methodological differences.…”
Section: Figmentioning
confidence: 77%
See 1 more Smart Citation
“…The forced swimming test (FST) was designed as a primary screening test for antidepressants, but the sensitivity of the FST in detecting TBI-induced depression has not been consistent. Although depression-like behavior during the FST has been reported previously in a mild TBI model using weight drop (Milman et al, 2005;Shapira et al, 2007), it was not detected in our current mouse TBI model, or in the fluid-percussion injury model ( Jones et al, 2008). Potential contributing factors to the differential detection of depression-like behavior by FST after brain injury may lie in differences in the models and severity of experimental TBI, the timing of the affective measures used following injury, and/or other methodological differences.…”
Section: Figmentioning
confidence: 77%
“…Similarly to human post-injury syndrome, a depressionlike state has been observed following episodes of TBI in laboratory animals (Milman et al, 2005). To determine the effects of TBI and the antidepressant fluoxetine on depressionlike behavior, mice were evaluated with the forced swimming test.…”
Section: Neither Tbi Nor Chronic Fluoxetine Treatment Affects Depressmentioning
confidence: 99%
“…The passive avoidance (PA) test was used to evaluate nonspatial, hippocampus-mediated contextual memory and fearrelated amygdala-dependent emotional memory 29 on PID 26-28. The one-trial step-through PACS-30 Passive Avoidance apparatus (Columbus Instruments, Columbus, OH) consisted of two adjoining compartments (24 · 23 · 27 cm), one lighted and one darkened, divided by a guillotine door.…”
Section: Passive Avoidance Testmentioning
confidence: 99%
“…Nonetheless, several excellent animal models of concussive injury have recently been established (Gurkoff et al, 2006;Henninger et al, 2005;Milman et al, 2005;Tang et al, 1997;Tashlykov et al, 2007;Ucar et al, 2006;Yoshiyama et al, 2005;Zohar et al, 2003Zohar et al, , 2006. For example, Henninger et al (2005) modifying methods of Tang et al (1997) have used a weight drop device to the exposed skull that replicates human concussion.…”
Section: Animal Models Of Concussionmentioning
confidence: 99%
“…However, histology demonstrated several pathological changes including a reduction in the number of cortical neurons as well as in the hippocampus. A limitation of this study is that it only examined memory nine days postinjury but Milman et al (2005) and Zohar et al (2003Zohar et al ( , 2006 using somewhat similar methods, but in mice, have demonstrated these type of persistent cognitive differences in concussed animals for longer periods of time post-injury. Gurkoff et al (2006) have demonstrated this in rats with a fluid percussion injury model and Tashlykov et al (2007) have shown apoptotic changes in cerebral cortex and hippocampus using this weight drop technique as well.…”
Section: Animal Models Of Concussionmentioning
confidence: 99%